A population database analysis to describe the residual burden of varicella in Italy—a high vaccination coverage area—from 2004 to 2022 - Barbieri, Elisa; Cocchio, Silvia; Furlan, Patrizia; Scamarcia, Antonio; Cantarutti, Luigi; Giaquinto, Carlo; Baldo, Vincenzo (Frontiers in Public Health, 2025)
IntroductionIn Italy, universal varicella vaccination (VV) started in 2017 with a two-dose schedule administered in children aged 12–15 months and 5–6 years, achieving 90% coverage in 2019, though with regional variations. To address the limitations in surveillance databases for capturing varicella episodes, the study aimed to evaluate the burden of varicella disease in the pediatric population using a primary care database.MethodsThis cohort study used data from Pedianet, a comprehensive database of 193 family pediatricians in Italy. The incidence rate (IR) of varicella (International Classification of Diseases, Ninth Revision, Clinical Modification [ICD-9-CM] codes 052 and 052.0–52.9) was evaluated in children aged below 15 years, from January 2004 to April 2022, categorized by calendar year and region. Subjects were followed up from 2004 or their enrollment date until the end of assistance or the study period. Comorbidities and complications were identified.ResultsA total of 253,221 children aged below 15 years (resulting in a total follow-up of 1,430,249 person-years) were included in the study. A total of 35,614 varicella index cases were identified in 35,199 subjects (13.9%), with 1.2% experiencing two infections. Complications following varicella occurred in 467 children (1.3%), primarily affecting the skin and soft tissue (46.3%) and the respiratory tract (22.3%). The IR in regions that implemented the VV program before 2017 ranged from 38.3 per 1,000 person-years in 2007 to 0.8 per 1,000 person-years in 2022, while in those that implemented the VV in 2017, the IR decreased from 49.8 per 1,000 person-years in 2017 to 3.2 per 1,000 person-years in 2022. In the Veneto Region, following the implementation of VV in 2006, the IR significantly decreased by 20.5 annually (95% CI: −23.4, −17.5), ranging from 50.2 per 1,000 person-years in 2006 to 1.2 per 1,000 person-years in 2022.ConclusionThe implementation of VV drastically reduced the IR of varicella, further confirming the importance of universal VV coverage.